Energy evolution: A new perspective on the failure mechanism of purplish-red mudstones from the Three Gorges Reservoir area, China - Wen, Tao; Tang, Huiming; Huang, Lei; Wang, Yankun; Ma, Junwei (Engineering geology, 2020)
•New energy-evolution perspective is provided on failure mechanism of b4 mudstones.•Energy-parameters estimation methods under cyclic loading-unloading are presented.•A parameter to measure proportion of CDE is introduced, which is defined as CDE/TAE.•Influence of stress path on mechanical properties and energy evolution is revealed. Purplish-red mudstones from Section Four of the Badong Formation are broadly distributed in the Three Gorges Reservoir area (TGRA) and exhibit special characteristics distinct from the mudstones elsewhere. This paper investigates the failure mechanism of such mudstones from a new perspective of energy evolution. Initially, the complete failure process under three stress paths (i.e., loading, unloading, and cyclic loading-unloading) is monitored, and the related data are acquired. Methods to estimate the energy parameters (i.e., total absorption energy (TAE), cumulative dissipation energy (CDE), and elastic strain energy (ESE)) under cyclic loading-unloading conditions are presented. Two new parameters, namely, the proportion of CDE (PCDE) and proportion of elastic energy dissipation (PEED), are introduced. Using the data, the mechanical properties and energy properties are analyzed, and the energy evolution is revealed. The results show that the failure mechanism under the three stress paths is different from an energy evolution perspective. The mechanical parameters deteriorate under unloading in comparison with those under loading. The increase in the CDE is similar to that in the TAE, and the ESE-strain relationship features a step-shaped rise. For cyclic loading-unloading, the TAE and the PCDE nearly linearly increase with cycle times. This work provides a new perspective on the failure mechanism of the purplish-red mudstones from the TGRA.